Peran Kepemimpinan di Era Multieduhealthtainment 5.0 - Zainudin, Ali; Z. Soeratin, Harry (IAIN Manado, 2023)
Leadership Roles in the Multieduhealthainment 5.0 era. Advances in information and communication technology have affected how we learn, stay healthy, and enjoy happiness for the gifts of Allah SWT, which are given with gratitude. Practical and flexible leadership is critical in dealing with difficulties and taking advantage of the possibilities provided by the 5.0 Digitalization era. Consequently, the authors were motivated to study leadership function in the Multieduhealthtainment 5.0 age. This period is different with multi-integration, education, health, and entertainment in one platform. Literature studies are utilized as a research tool to understand leadership in the Multieduhealthtainment 5.0 era. According to the study's results, leaders of this century must possess the skills and expertise needed to manage multifaceted educational, health, and entertainment systems effectively